Making the water move: techno-historic limits in the game aesthetics of Myst and Doom. - Hutchison, Andrew (Game Studies, 2008)
This paper proposes that the technical limitations at the time of a game?s creation have an enormous impact on the overall aesthetic of any specific game, and also the traditions of the whole craft. Thus, an awareness of this aspect is critical to the useful analysis of games. However, this is often missing from current analyses of games. To illustrate both the significance of techno-historic limits, and several fundamental principals of digital technology, the landmark games Myst (Cyan, 1993) and Doom (id Software, 1993) are explored as examples of the evolution of game aesthetics over time. This leads to an examination of the future limits of the rendering of images and sounds, and how this may have an impact on future game aesthetics and genres.